Broadband low-frequency sound absorption in open tunnels with deep sub-wavelength Mie resonators - Xia, Jianping; Sun, Ye-Yang; Guan, Yi-Jun; Wang, Yin; Lu, Yu-Jing; Hu, Hui-Gang; Ge, Yong; Sun, Hong-Xiang; Yuan, Shou-Qi; Lai, Yun; Liu, Xiao-Jun (Frontiers in Physics, 2022)
We report both experimentally and numerically that near-perfect absorption of low-frequency sound is realized in an open tunnel embedded with two deep sub-wavelength (0.085λ) Mie resonators. The resonators are composed of a multiple-cavity structure and an outer frame on three sides. In the eigenmode analysis, we obtain two types of monopolar Mie resonance modes (MMR I&II) in a single resonator around 250Hz. The eigenfrequency of MMR I is mainly determined by the Helmholtz resonance of each cavity in the multiple-cavity structure, while that of MMR II is closely related to the coupling between the multiple-cavity structure and its outer frame, showing high performances of coupling and sound absorption. Based on the thermal viscous loss of sound energy in the channels created by the mutual coupling of MMR II of both Mie resonators with different diameters, the near-perfect sound absorption through the open tunnel is realized around 283Hz. More interestingly, by increasing the number of Mie resonators in the tunnel, a broadband near-perfect sound absorption is observed, and the fractional bandwidth can reach about 0.25 and 0.46 for the tunnels with 6 and 13 resonators, The proposed deep sub-wavelength Mie resonator and its associated near-perfect sound absorptions have great potential applications in architectural acoustics.